(Women Writing) The Modernist Line - Cristanne Miller (Association Française d'Etudes Américaines, 2017)
Of the five English-language poets who experimented most radically with the poetic line in the 1910s, four were women: Mina Loy, H.D., Marianne Moore, and to a lesser extent Gertrude Stein, since she rejected the poetic line altogether in Tender Buttons. The crucial moves away from Whitman’s nineteenth-century aesthetic had to do with the line as seen, as independent of syntax and meter, as restructuring the possibilities of rhyme, and as a unit in tension with other aspects of form, narrative, and voice in a poem. In the hands of these women, the modernist line had appeared in almost every radical configuration of high modernism by the end of 1917. This paper explores the particular innovations of these women in relation to the structures of the modernist poetic line.